2012
DOI: 10.1007/s10709-012-9668-3
|View full text |Cite
|
Sign up to set email alerts
|

Sex chromosomes and associated rDNA form a heterochromatic network in the polytene nuclei of Bactrocera oleae (Diptera: Tephritidae)

Abstract: The olive fruit fly, Bactrocera oleae, has a diploid set of 2n = 12 chromosomes including a pair of sex chromosomes, XX in females and XY in males, but polytene nuclei show only five polytene chromosomes, obviously formed by five autosome pairs. Here we examined the fate of the sex chromosomes in the polytene complements of this species using fluorescence in situ hybridization (FISH) with the X and Y chromosome-derived probes, prepared by laser microdissection of the respective chromosomes from mitotic metapha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
32
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 71 publications
3
32
0
1
Order By: Relevance
“…Although research related to rRNA in diptera is scarce, we found that in many species of culicidae (Rafael et al, 2006) and tephritidae (Drosopoulou et al, 2012), the rRNA genes are usually localized in sex chromosomes; however, in some cases (e.g., Rhagoletis pomonella), it can be found in autosomal chromosomes (Procunier and Smith, 1993).…”
Section: Discussionmentioning
confidence: 73%
“…Although research related to rRNA in diptera is scarce, we found that in many species of culicidae (Rafael et al, 2006) and tephritidae (Drosopoulou et al, 2012), the rRNA genes are usually localized in sex chromosomes; however, in some cases (e.g., Rhagoletis pomonella), it can be found in autosomal chromosomes (Procunier and Smith, 1993).…”
Section: Discussionmentioning
confidence: 73%
“…Other protocols require the pooling of many (typically 10-30) chromosome fragments in order to successfully amplify the sample 7,11,28,40 . Although pooling of multiple chromosomes is possible using our method, the increased likelihood of sample contamination emphasizes the importance of beginning the experiment with as few chromosomes as possible.…”
Section: Discussionmentioning
confidence: 99%
“…This method is also applied to studying the 3D dynamics of chromosome territories in development 9 and pathology 10 . Differentially labeled chromosome paints are used for the visualization of individual mitotic 11,12 , meiotic 13,14 , or interphase non-polytene 15,16 and polytene 9,11,17 chromosomes. A simple and robust protocol to obtain chromosome paints would be very useful in expanding this technique to non-model organisms, such as mosquitoes.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations